Characteristics of the spiny dogfish (Squalus acanthias) nuclear genome - Wagner, C Isabel; Kopp, Martina E L; Thorburn, James; Jones, Catherine S; Hoarau, Galice; Noble, Leslie R (Genetics Society of America, 2023)
Sequenced shark nuclear genomes are underrepresented, with reference genomes available for only four out of nine orders so far. Here we present the nuclear genome, with annotations, of the spiny dogfish (Squalus acanthias), a shark of interest to biomedical and conservation efforts, and the first representative of the second largest order of sharks (Squaliformes) with nuclear genome annotations available. Using Pacific Biosciences Continuous Long Read data in combination with Illumina paired-end and Hi-C sequencing, we assembled the genome de novo, followed by RNA-Seq-supported annotation. The final chromosome-level assembly is 3.7 Gb in size, has a BUSCO completeness score of 91.6%, and an error rate of less than 0.02%. Annotation predicted 33,283 gene models in the spiny dogfish’s genome, of which 31,979 are functionally annotated.